A model of demand for Islamic Banks’ debt-based financing instruments - Mansor Jusoh,; Norlin Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2013)
This paper presents a theoretical analysis of the demand for debt-based financing instruments of the Islamic banks. Debt-based financing, such as through bai bithaman ajil and al-murabahah, is by far the most prominent of the Islamic bank financing system and yet it has been largely ignored in Islamic economics literature. Most studies instead have been focusing on equity-based financing of al-mudarabah and al-musyarakah. Islamic banks offer debt-based financing through various instruments derived under the principle of exchange or more specifically, the deferred contract of exchange. In this paper we set an analytical framework that is based on an infinitely lived representative agent model to analyze the demand for goods to be purchased by deferred payments. The resulting demand will then be used to derive the demand for Islamic debt. We also investigate theoretically, factors that may have an impact on the demand for Islamic debt.